M-COMMERCE AND ITS LEGAL ISSUES - shukri, Sakinah mohd; Azam, S.M. Ferdous; Johar; MGM (International Journal of Psychosocial Rehabilitation, 2020)
According to a study done by IDC in 2005, there is a total of 259,629 handheld devices were shipped to the Malaysian market in 2004, which is a 90% increase over 2003. Most of the handheld devices today provide Internet connection capabilities. In most cities in Malaysia, particularly in Klang Valley, many places are equipped with wireless Internet connection or WiFi (wireless fidelity). Trends in ICT generally concentrate on the devices such as mobile phones or PDA. Some of the mobile phone comes with Internet connection capabilities. With the Internet through personal computers emerged the electronic commerce, thus with the WiFi connectivity being the latest trend in mobile devices, the rise of mobile commerce is expected.